(untitled) - Moore, Michael G. (Belmont, California, 1996)
The only comprehensive and current text on the subject of distance education; utilizes a systems approach to organize and justify material and includes information on the fundamental issues of distance education as well as the theory, research, and practice.
Keywords: Distance education; United States